2018
DOI: 10.23736/s1824-4785.18.03090-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of amino-acid PET in the light of the new WHO classification 2016 for brain tumors

Abstract: Since its introduction in 2016, the revision of the World Health Organization (WHO) classification of central nervous system tumors has already changed the diagnostic and therapeutic approach in glial tumors. Blurring the lines between entities formerly labelled as "high-grade" or "low-grade", molecular markers define distinct biological subtypes with different clinical course. This new classification raises the demand for non-invasive imaging methods focusing on depicting metabolic processes. We performed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In light of the new WHO molecular classification for brain tumors (2016), the possible influence of genomic markers on the degree of amino acid radiopharmaceuticals uptake has been discussed [ 18 ]. The role of amino acid radiopharmaceuticals in tumor grading and patient prognosis is well confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the new WHO molecular classification for brain tumors (2016), the possible influence of genomic markers on the degree of amino acid radiopharmaceuticals uptake has been discussed [ 18 ]. The role of amino acid radiopharmaceuticals in tumor grading and patient prognosis is well confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The study mainly explored the relationship between this parameter and clinical biological data (including IDH1 mutation status, 1p/19q codeletion and MGMT promoter methylation), describing a significant correlation with histological grade and IDH1 mutation status [6]. Moreover, previous data suggested [ 18 F] FET PET imaging may allow a non-invasive evaluation of IDH mutation status in gliomas [7,8], even if IDH mutated and 1p/19q co-deleted oligodendrogliomas cannot be differentiated from glioblastomas and astrocytomas by [ 18 F] FET PET [7].…”
Section: Introductionmentioning
confidence: 99%
“…The classification contained some well-known biomarkers, such as MGMT methylation, 1p/19q co-deletion, IDH 1 or 2, and EGFR. Recently, Suchorska et al reported that amino acid positron emission tomography (PET)-based metabolic imaging can be used as a promising tool for the non-invasive characterization of molecular features and to provide additional prognostic information (19). These classifications and studies helped with prognosis, survival time, and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these issues, radiolabeled amino acid tracers are preferred, and the repertoire of such molecules continues to expand [ 34 37 ]. Clinical applicability includes the delineation of tumor extent, especially in normal-appearing tissue where it can aid in radiotherapy and surgical planning [ 38 ]. Assessment of treatment response by amino acid PET is gaining interest.…”
Section: Imaging Techniques To Aid In Diagnosismentioning
confidence: 99%